Gestural interaction with 3D objects shown on public displays - Du, Guiying (2018)
Du, G., Degbelo, A., Kray, C., & Painho, M. (2018). Gestural interaction with 3D objects shown on public displays: An elicitation study. Interaction Design and Architecture(s), 2018(38), 184-202.